Peranan Sistem Informasi Akuntansi Auk Solution Terhadap Efisiensi dan Efektivitas Operasional pada Mesin Injection di PT XYZ - Roup, Abdul (Jurnal Informatika Kesatuan, 2024)
This study aims to evaluate the impact of using the Auk Solution accounting information system on the efficiency and effectiveness of injection machine operations at PT XYZ. Data were collected from machine cycle time reports, Overall Equipment Effectiveness (OEE) analysis, and energy monitoring over a specific period. The research results indicate a significant increase in operational efficiency and a reduction in energy costs following the implementation of the Auk Solution system.. Keywords: , Overall Equipment Effectiveness (OEE). Energy monitoring, Scada